(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Tinnitus is a phrase that refers to the conscious experience of an auditory sensation in the absence of a corresponding external stimulation. It is derived from the Latin verb tinnire, which means "to ring.’. In recent few years, it has been found that among 101 causes of tinnitus, cervical and TMJ disorders are one of the leading cause of it. The aim of this study is to evaluate the association and perception of tinnitus among the patients having pain in cervical and TMJ region. This study was cross sectional study and was conducted on the population of the ULTH, Gangaraam hospital. It includes both male and female patients. A survey was sent out through email to 145 patients. Their role was to complete an updated expert revised survey testing their association of tinnitus with cervical or TMJ region pain. Descriptive statistics was applied to conclude results.The mean age of population was 35.53 with the standard deviation ± of 12.176 of data. Out of 145 patients. 93 (64.1%) were males and 52 (35.9%) were females. The study reveals that association of tinnitus with cervical and TMJ pain was more common in males. Females had a low rate of tinnitus with cervical and TMJ painThe study reveals that association of tinnitus with cervical and TMJ pain was more common in males. Females had a low rate of tinnitus with cervical and TMJ pain. The Pearson chi square association is statistically significant (P=0.016).